Cooperativity flows and shear-bandings: a statistical field theory approach. Issue 2 (21st October 2015) - Benzi, R.; Sbragaglia, M.; Bernaschi, M.; Succi, S.; Toschi, F.
Abstract : Cooperativity effects have been proposed to explain the non-local rheology in the dynamics of soft jammed systems. Abstract : Cooperativity effects have been proposed to explain the non-local rheology in the dynamics of soft jammed systems. Based on the analysis of the free-energy model proposed by L. Bocquet, A. Colin and A. Ajdari, Phys. Rev. Lett., 2009, 103, 036001, we show that cooperativity effects resulting from the non-local nature of the fluidity (inverse viscosity) are intimately related to the emergence of shear-banding configurations. This connection materializes through the onset of inhomogeneous compact solutions (compactons), wherein the fluidity is confined to finite-support subregions of the flow and strictly zero elsewhere. The compacton coexistence with regions of zero fluidity ("non-flowing vacuum") is shown to be stabilized by the presence of mechanical noise, which ultimately shapes up the equilibrium distribution of the fluidity field, the latter acting as an order parameter for the flow–noflow transitions occurring in the material.